Культурно-історичні витоки ідеї підготовки національної гуманітарно-технічної еліти - Романовський, Олександр Георгійович; Пономарьов, Олександр Семенович (НТУ "ХПІ", 2009)
It is shown that to the 125year the National technical university the "Kharkov polytechnic institute" befits with serious successes not only in professional preparation but also in spiritual and cultural development of students. The substantive provisions of the offered conception of forming of national humanitarian-technical elite and its cultural and historical roots are exposed. Essence and maintenance of the phenomenon of elite and different going is analysed near its understanding.
Cultural and historical sources of idea of national humanitarian-technical elite preparation
Keywords: вища школа; вища технічна освіта; 125-річчя НТУ "ХПІ"; історія НТУ "ХПІ"; науковий здобуток; інженерна освіта